2014
DOI: 10.1186/1748-7161-9-6
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between compliance and brace treatment in juvenile and adolescent idiopathic scoliosis: SOSORT 2014 award winner

Abstract: BackgroundOver the last years, evidence has accumulated in support of bracing as an effective treatment option in patients with idiopathic scoliosis. Yet, little information is available on the impact of compliance on the outcome of conservative treatment in scoliotic subjects. The aim of the present study was to prospectively evaluate the association between compliance to brace treatment and the progression of scoliotic curve in patients with idiopathic adolescent (AIS) or juvenile scoliosis (JIS).MethodsAmon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(70 citation statements)
references
References 30 publications
(33 reference statements)
2
62
1
3
Order By: Relevance
“…Another limitation of the study is the lack of a control group (i.e., untreated patients), but no ethics committee would allow not to treat structured and progressive scoliosis ranging from 25 to 40° Cobb at 10–12 years of age. Nevertheless, in another our study, it was demonstrated that in all our cases in which the brace is not worn correctly the evolutionary process of scoliosis, confirming its evolutivity, is resumed [ 27 ] and recently the efficacy of the brace against the control group was confirmed also in other paper [ 18 ].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Another limitation of the study is the lack of a control group (i.e., untreated patients), but no ethics committee would allow not to treat structured and progressive scoliosis ranging from 25 to 40° Cobb at 10–12 years of age. Nevertheless, in another our study, it was demonstrated that in all our cases in which the brace is not worn correctly the evolutionary process of scoliosis, confirming its evolutivity, is resumed [ 27 ] and recently the efficacy of the brace against the control group was confirmed also in other paper [ 18 ].…”
Section: Discussionsupporting
confidence: 67%
“…In particular, bracing discontinuation up to 1 month does not impact on the treatment outcome. Conversely, wearing the brace only overnight is associated with a high rate of curve progression [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Blount et al [ 37 ] originally described full-time brace wear as 23 hours a day and Rowe et al [ 5 ] found that bracing for 23 hours a day was the most successful means in their meta-analysis. Aulisa et al [ 38 ] also stated that wearing the brace only overnight was associated with a high rate of curve progression. Indeed, the guidelines released by the Society on Scoliosis Orthopaedic and Rehabilitation Treatment (SOSORT) indicate adherence as a key element in determining the efficacy of bracing [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…1 However, compliance with the prescribed regimen is an issue and reduced compliance has consistently been shown to affect treatment outcome. [1][2][3][4] Because of these issues, a part-time brace design was developed. This brace was designed to provide a higher level of curve correction allowing for nighttime use only.…”
Section: Introductionmentioning
confidence: 99%